BACTERIAL EFFECTS ON THE MOBILIZATION OF CATIONS FROM A WEATHERED PB-CONTAMINATED ANDESITE - Fein J.B.; Brady P.V.; Jain J.C.; Dorn R.I.; Lee J.U. (My University, 1999)
Mobilization of contaminant Pb and other cations from a weathered andesite was examined by conducting water-rock leaching experiments to measure release rates of the major and minor elements found in the bulk rock. Experiments were conducted for over 600 h, at pH 3 and 6.5, as a function of grain size, and in the presence and absence of a common subsurface bacterial species, Bacillus subtilis. The acid leaching experiments exhibited enhanced Pb mobilities. The contact area between mineral surfaces and water controlled the amount of most elements leached into solution. Typically, bacteria accelerated the leaching of trace elements. However, major element levels were inversely correlated with bacterial content, and generally lower major element concentrations were observed in the presence of bacteria, relative to the bacteria-free systems. This effect was likely caused by bacterial enhancement of secondary mineral precipitation rates. Extremely low concentrations of Pb were leached into solution during the course of the experiments under conditions most closely approximating natural conditions (i.e., near neutral pH). Moreover, the release rate of Pb relative to other elements was low. Pb was associated with iron oxides precipitated in the rock pore spaces, and the experiments suggest that the iron oxides dissolved to a lesser extent than did other minerals in the rock matrix. The mobility of the Pb associated with these iron oxides was less than that of other heavy metals that were likely associated with the surrounding matrix.
Keywords: BACTERIA; LEACHING; WEATHERING; DISSOLVED MATERIALS; LEAD; BIOCHEMISTRY